Comorbid fibromyalgia in migraine patients: clinical significance and impact on daily life. (3rd October 2019) - Onder, Halil; Hamamci, Mehmet; Alpua, Murat; Ulusoy, Ersin Kasım
ABSTRACT: Objective : Herein, we aimed to investigate the impact of FM in migraine patients and the specific features and discriminations of this group of migraineurs with FM according to patients without FM. Methods : 102 consecutive migraine patients among 18–50 years old who accepted to involve in the study were included. All patients were asked to complete the following self-report questionnaires for the assessment of pain-related disability, migraine-related disability, anxiety, depression, sleep disturbance and quality of life. All statistical analyses were performed using the SPSS statistics 20 program. Results : 92% of the patients were diagnosed with episodic migraine, whereas 8% of them was diagnosed with chronic migraine (CM). Comorbid FM which was detected to present in 30.3% of the patients. FM was more frequent in CM patients and in migraine patients with aura. The analyses comparing FM (+) and FM (-) migraineurs revealed that headache frequency, migraine disease duration, headache impact test, MIDAS scores were significantly higher in FM (+) migraineurs. Furthermore, the vitality and role-emotional domains of the SF-36 resulted in worse scores in the group of FM (+) migraineurs. Conclusion : The results of our study may suggest the presence of FM as a clinical sign of a more severe migraine. However, the long-term prospective studies including these group of patients are needed to understand the prognostic impact and importance of the comorbid FM in migraine. Abbreviations: FM: Fibromyalgia; MIDAS: Migraine Disability Assessment